Girolamo Frescobaldi (1583-1643), engraving by Claude Mellan (1619) - Claude Mellan (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Girolamo Frescobaldi (1583-1643), engraving by Claude Mellan (1619). The Italian composer Girolamo Frescobaldi (Ferrara, 1583 - Rome, 1643), engraving by Claude Mellan (1619).
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons